Journalistic Code of Ethics, ITE Law and Social Phenomena in Social Media - Suciono, Wahyu (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
Journalistic language must meet a number of requirements, such as appearing attractive, varied, fresh, with character. In addition, he must always appear concise and straightforward, logical, dynamic, democratic and populist. The journalistic Code of Ethics was created in order to accommodate and safeguard the exercise of press freedom carried out with full awareness, responsibility and professionalism by press actors. Based on the ITE Law, electronic information is one or a set of electronic data, including but not limited to writing, voice, images, maps, designs, photographs, electronic data interchange (EDI), electronic mail, telegrams, telex, telecopy or the like, letters, signs, numbers, access codes, symbols, or processed perforations that have meaning or can be understood by people who are able to understand them. The positive impact of social phenomena provides a benefit for both oneself and others such as modernization which creates effectiveness and efficiency at work, a culture of mutual cooperation creates a clean and comfortable environment and so on.